The Influence of Vegetation and House Index on Male Mosquitoes DHF Vector Abundance on Kawengen Sub-District (Unnes Journal of Public Health, 2020)
The environmental conditions of an area can be a major risk factor for potential outbreaks of DHF. Dense areas with a variety of vegetation are facilitated as breeding sites and have an impact on vector density. The high of vector population give an effect the speed of transmission vector-borne diseases. DHF vector population is related to the vector DHF mating pattern. Adult male mosquitoes vector DHF plays an important role in the pattern of mating DHF. The proportion of mating between adult male and females mosquitoes is 1: 1. Thus it can be seen the density of male mosquitoes, it can be easily estimated the number of female mosquitoes which fertilize and lay eggs. Conducted using observational analytics with male mosquito population surveillance approach. This research aimed to effect of vegetation and House Index (HI) on the abundance of male mosquito populations. Adult mosquitoes taken using light traps with a total sampling technique. Using spatial vegetation analysis shows that Kawengen residents, has a variety of monoecious groups and rice fields. Variety of fruit trees (banana,mango,guava,soursop), flower plants (frangipani,hibiscus), bamboo, another plant (i.e teak). Vegetation density is in the low-moderate category. Kawengen included in the category of moderate density (HI=36%). The number of Aedes sp. male mosquitoes trapped by light traps, of the total trapped mosquito was 6.52%. Variety and density of plants give a support the abundance of male mosquitoes. As a resting and feeding place. HI in moderate density category, indicates there is a positive container or a place for laying eggs. The larvae density affects the sex ratio of mosquitoes.